SISTEM PELAPORAN AKUNTANSI ZAKAT PADA BADAN AMIL ZAKAT (BAZ) BOJONEGORO - Nurul Mazidah; Istirokah Istirokah (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
This study describes how the accounting reporting system practiced Agency Amil Zakat (BAZ) Bojonegoro, the implications of the accounting reporting system to the accountability of the organization and practiced BAZ statements have not been in accordance with Statement of Financial Accounting Standards (SFAS) No. 45 on financial reporting Nonprofit Organization Management including Zakat. The method used in this study is a case study, Population financial reports were used BAZ 2001 to 2009. Interview data collection methods, observation and book study while the data analysis techniques that use horizontal analysis and qualitative analysis. Research Shows There are differences between the financial statements of Entity Amil Zakat (BAZ) Bojonegoro to report in accordance with Statement of Financial Accounting Standards (SFAS) no. 45. About financial reporting organisasi Nonprofit Organization Management including Zakat.